2010
DOI: 10.1089/jwh.2009.1856
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Chronic Pain in Survivors of Intimate Partner Violence

Abstract: These findings can inform clinical care of women with chronic pain in all areas of healthcare delivery by reinforcing the importance of assessing for a history of child abuse and IPV. Moreover, they highlight the relevance of routinely assessing for abuse-related injury and PTSD and depressive symptom severity when working with women who report chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
46
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 66 publications
(61 reference statements)
7
46
0
5
Order By: Relevance
“…Moreover, studies consistently have shown that traumatic experiences are associated with the development of persistent pain (Hart- Johnson and Green, 2012; Paras et al, 2009; Wuest et al, 2010). This relationship may exist due to an increased vulnerability to stress and an altered and prolonged stress response (Dudley et al, 2011).…”
Section: Persistent Pain and Traumatic Experiencesmentioning
confidence: 99%
“…Moreover, studies consistently have shown that traumatic experiences are associated with the development of persistent pain (Hart- Johnson and Green, 2012; Paras et al, 2009; Wuest et al, 2010). This relationship may exist due to an increased vulnerability to stress and an altered and prolonged stress response (Dudley et al, 2011).…”
Section: Persistent Pain and Traumatic Experiencesmentioning
confidence: 99%
“…The reporting of pain symptoms with functional impairment is also independent of the military service period and is seen across the board for World War II, Korean war, Vietnam war, Persian Gulf war (PGW), and OIF/OEF Veterans [14][15][16][17][18][19]. Among adult survivors of physical, psychological, or sexual abuse, the most common types of chronic pain include pelvic pain, lower-back pain, facial pain, and bladder pain, along with a high prevalence of fibromyalgia [20][21]. In OIF/OEF over the past 10 years, there has been increased interest in the relationship between PTSD and chronic pain.…”
Section: Intersection Of Ptsd and Painmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention defines IPV as ''physical violence, sexual violence, threats of physical/sexual violence, and psychological/emotional abuse perpetrated by a current or former spouse, common-law spouse, nonmarital dating partners, or boyfriends/girlfriends of the same or opposite sex.'' 4,5 Previous studies have linked IPV to a wide range of adverse health consequences, including injury, 3,[6][7][8] chronic pain, 9,10 gastrointestinal disorders, [11][12][13] sexually transmitted diseases, [14][15][16][17] disability, 18,19 poor pregnancy outcomes, 20 substance abuse, [21][22][23] depression, 24,25 post-traumatic stress disorder (PTSD), 26,27 and death. 28 Clearly, a gender gap exists in susceptibility to violence in general and IPV in particular, with most national surveys suggesting higher IPV rates in women versus men.…”
mentioning
confidence: 99%